E-Commerce for Added Potential of Management for Ban Pa-ao Bronzeware Center - อินทะแสง, ขนิษฐา; โชติพันธ์, ธีรดา; กิจเพิ่มเกียรติ, สันทนีย์ (Journal of Roi Et Rajabhat University, 2017)
The development of e-commerce system for added potential of management for Ban Pa-ao Bronzeware Center was aimed to expand marketing coverage, to increase distribution channels, to be a source of knowledge for the public to learn about Ban Pa-ao bronzeware, and to promote and support the potential development of the local wise men. This e-commerce system was developed as a web page on Window XP by using PHP script language and MySQL database program. The PHP was applied to design and develop a user interface whereas the MySQL database was used as the database server. The program is divided into two sessions; the customer and the staff. The customer session consists of the membership section, basket trading system, product searching, customer service, and a receipt-invoice process. The staff session consists of the subscribing system, membership system, ordering, payment system, and FAQ. The system was evaluated with a survey from twenty-eighth users including 5 staff members, 10 members, and 13 nonmembers. The results of the study were as follows: The evaluation of this system showed that users rated moderate to the highest levels of satisfaction toward the developed e-commerce. And the majority of the users (77.85%) were satisfied at a high level. This finding might be due to the reason that the system provided more channels to distribute products. It helped disseminate the local knowledge of bronzeware. It also supported the potential development of the local wisdom as a purpose of the study.